1998
DOI: 10.1161/01.hyp.32.6.1094
|View full text |Cite
|
Sign up to set email alerts
|

G-Protein β3 Subunit Gene ( GNB3 ) Variant in Causation of Essential Hypertension

Abstract: Abstract-Essential hypertensives display enhanced signal transduction through pertussis toxin-sensitive G proteins. The T allele of a C825T variant in exon 10 of the G protein ␤3 subunit gene (GNB3) induces formation of a splice variant (G␤3-s) with enhanced activity. The T allele of GNB3 was shown recently to be associated with hypertension in unselected German patients (frequencyϭ0.31 versus 0.25 in control). To confirm and extend this finding in a different setting, we performed an association study in Aust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
123
3
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(139 citation statements)
references
References 25 publications
10
123
3
3
Order By: Relevance
“…Another possibility is that the contribution of GNB3 gene to the pathogenesis of EH may be less significant than initially implied in the previous population studies, partly because of ethnicity-specific combination of genetic backgrounds and environmental factors. The frequency of the 825T allele in the present subjects was remarkably higher (50.1%) than that reported in Amerindians (26.5%) and western Europeans (29.6%), 32 but was similar to that described in Taiwan Han Chinese (54.3%), 29 northern Chinese (52%), 25 Canadian Oji-Cree (50.1%) 37 and Japanese populations (49%). 33 On the other hand, the frequency of the 825T allele in our population was much lower than that in Africans (79%), whereas it was slightly higher than the southern Chinese population (43.2%) reported by Siffert et al 37 As for the ACE I/D polymorphism, the D allele of the ACE gene is reportedly associated with the development of EH.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Another possibility is that the contribution of GNB3 gene to the pathogenesis of EH may be less significant than initially implied in the previous population studies, partly because of ethnicity-specific combination of genetic backgrounds and environmental factors. The frequency of the 825T allele in the present subjects was remarkably higher (50.1%) than that reported in Amerindians (26.5%) and western Europeans (29.6%), 32 but was similar to that described in Taiwan Han Chinese (54.3%), 29 northern Chinese (52%), 25 Canadian Oji-Cree (50.1%) 37 and Japanese populations (49%). 33 On the other hand, the frequency of the 825T allele in our population was much lower than that in Africans (79%), whereas it was slightly higher than the southern Chinese population (43.2%) reported by Siffert et al 37 As for the ACE I/D polymorphism, the D allele of the ACE gene is reportedly associated with the development of EH.…”
Section: Discussionsupporting
confidence: 72%
“…34 On the contrary, a number of studies of Caucasians have confirmed an association between the 825T allele and EH. 25 In addition, a statistical significant interaction between the 825T allele and obesity was investigated for SBP in the Brazilian population. 35 Interestingly, in contrast to the above findings, the C rather than the T allele was associated with increasing SBP without gender effect in Canadian Oji-Cree.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Siffert et al 10 described a C825T polymorphism in G-protein b-3 subunit (GNB3), the gene encoding for the b-3 subunit of heterotrimetric G-proteins, and reported a significant association of the 825T allele with EH in 426 unselected patients in Germany. This genetic finding was supported by other associate study in Europeans, 11 Australian white populations, 12 and Canadian aborigines, 13 but in African Americans 14 have proved conflicting.…”
Section: Introductionsupporting
confidence: 63%
“…Several groups have reproduced the original finding that the GNB3 825T allele is associated with hypertension, whereas other groups refuted that finding Schunkert et al 1998;Benjafield et al 1998;Brand et al 1999;Dong et al 1999, to cite but a few). The fact that there is a considerable variance in genotype distribution within different ethnicities (Siffert et al 1999) creates a major problem.…”
Section: Genetic Variants In the Gene For The Gα Subunit (Gnas) And Tmentioning
confidence: 99%